Comparison of Gravity Anomalies from Recent Global Geopotential Models with Terrestrial Gravity and Airborne Gravity over Johor Region - Rambat , Shuib; Mohamad Abdullah, Nazirah; Yaacob, Norehan; Othman, Nor' Azizi; Abidin, Zainal (International Journal of Integrated Engineering, 2021)
Gravity anomalies can yield an indirect but extremely useful picture of lateral changes in rock composition and structural patterns especially for rapid development area such as Johor region. The gravity anomalies can be derived from Global Geopotential Model (GGM) which is one of special product from the satellite technology that able to determine high accuracy of the earth’s gravity field. In this study, the gravity anomalies derived from recent GGM published by International Global Geopotential Model were compared with five other GGMs model that compromised either terrestrial or airborne or both to derive the gravity anomalies. In order to identify the best gravity model over the Johor region, two types of GGM class model has been selected for the comparisons which known as satellite only and combined class model. The result shows that the gravity anomalies de-rived from satellite only class model with up 300 spherical harmonic coefficients is the best fit model and can be used as a reference for the Johor region. The RSME for the recent GGM via satellite only were +/- 5.865 and +/- 3.347 mGal for terrestrial and airborne gravity anomalies respectively compared to other GGM.